Network of Sentence-Level Constructions - Piyamahapong, Piroon (Language and Linguistics, 2023)
Polysemy, a linguistic phenomenon whereby a single form conveys multiple but related senses, is pervasive in various languages, including Thai. However, explaining cases in which polysemous lexemes occur in different syntactic contexts by adopting a lexicalist approach is not straightforward due to the indefinite proliferation of grammatical and semantic properties of the lexeme under investigation. This study thus aims to provide a unified account for earlier cases from a constructionist perspective by establishing a network of sentence-level constructions. Constructions with the verb tôk (‘to fall’) were selected to determine whether grammatical constructions within a constructicon are interconnected. Contexts with tôk were collected from Thai National Corpus under the Patronage of Her Royal Highness Princess Mahachakri Sirindhorn (TNC). Analyses reveal that the verb tôk appears in five constructions: intransitive motion constructions, caused-motion constructions, serial verb constructions, resultative constructions, and periphrastic causative constructions. These constructions are not independent but are interconnected in a network labeled as a constructional network. Based on similarities of structural patterns and schematic constructional meanings, the first two constructions are closely related and form one part of the network. Another part is made up of the other three constructions. The intransitive motion construction connects these two constitutive parts to create the entire network of sentence-level constructions with the verb tôk. In addition to illustrating the constructional network of sentence-level constructions, this study demonstrates that the horizontal relations between constructions reflect the correspondence between falling event as expressed by the verb tôk, and other events, which are the constructional meaning of each construction.